The Role of GeneXpert MTB/RIF in Reducing Treatment Delay Among Multidrug Resistance Tuberculosis Patients: A Propensity Score Matched Analysis - Tamirat KS; Kebede FB; Baraki AG; Akalu TY (Infection and Drug Resistance, 2022)
Koku Sisay Tamirat,1 Fentahun Bikale Kebede,2 Adhanom Gebreegziabher Baraki,1 Temesgen Yihunie Akalu1 1Department of Epidemiology and Biostatistics, Institute of Public Health, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Ethiopia Public Health Institute, Addis Ababa, EthiopiaCorrespondence: Koku Sisay Tamirat, Email kokusisay23@gmail.comBackground: GeneXpert MTB/RIF testing is a rapid molecular diagnostic test that is performed with an automated cartilage-based machine that makes treatment initiation prompt. This study aimed at evaluating the impact of GeneXpert in the reduction of treatment delay among multidrug-resistant tuberculosis (MDR-TB) patients in Amhara regional state of Ethiopia.Methods: A facility-based retrospective follow-up study was conducted from January to February 2019, and a total of 465 MDR-TB patients were included in the study. Socio-demographic, clinical, and treatment-related characteristics were collected from patient’s chart retrospectively using data abstraction sheets. Binary logistic regression model was fitted to identify factors associated with treatment delay; adjusted odds ratio (AOR) with a 95% confidence interval (CI) was computed to assess the strength of association. A propensity score-matched (PSM) analysis was used to assess the impact of the GeneXpert MTB/RIF test on treatment delay through calculation of average treatment effect (ATE).Results: The majority, 92.4%, of patients had the pulmonary form of TB, and 46.7% of patients were diagnosed by GeneXpert MTB/RIF. The presence of cavitation (AOR = 0.62, 95% CI: 0.39 0.96), extrapulmonary form of TB (AOR = 0.34, 95% CI: 0.14 0.81), and GeneXpert (AOR = 0.15, 95% CI: 0.10 0.24) were factors associated with treatment delay. The average treatment effect (ATE) of PSM analysis showed that GeneXpert MTB/RIF has significantly reduced treatment delay by 41% compared to matched control groups.Conclusion: This study revealed that GeneXpert test has a strong association with the reduced treatment delays among MDR-TB patients. This underscores that rapid molecular tests could help improve the health system and lead to prompt initiation of MDR-TB treatment. Therefore, expansion and decentralization of GeneXpert tests to peripheral health facilities are highly recommended. In turn, the case detection and control of the disease will be hastened.Keywords: drug-resistant tuberculosis, treatment delay, Ethiopia